Sight, Sound, and Sense - Sebeok, Thomas A. (Indiana University Press, 1978)
"Semiotics: A Discipline or an Interdisciplinary Method?" -the query with which the internationally celebrated scholar Umberto Eco has titled his contribution to this volume-articulates a question raised in many quarters and will evoke interest among specialists not only in semiotics but also in communication, linguistics, literary criticism, and anthropology. The thirteen essays in this collection are the outcome of a pilot program in Semiotics in the Humanities held at Indiana University during the 1975-76 academic year. The lectures, a highlight of the program, are here produced in revised form. They fall under four major headings: historiography, with two articles, one on the origins of semiotics and the other on Peirce's theory of signs; methodology, which includes three articles that consider Eco's query and discuss the relation between social communication and semiosis; nonverbal communication, explored among animals and in man, with a focus on sign language in general; culture theory, religion, text analysis, and translation. Sight, Sound, and Sense, together with its companion volume, A Perfusion of Signs (Indiana University Press, 1977), examines the main trends in semiotic theory and praxis and supplies suitable reading in semiotics courses, on both introductory and advanced levels.